Role of 3D double inversion recovery in detecting multiple sclerosis using 3 tesla MRI system in Saudi Arabia - Almutairi, Abdullah Dhaifallah N (2021)
Background: Magnetic Resonance Imaging (MRI) is one of the diagnostic imaging modalities employing in lesion detection in neurological disorders such as Multiple Sclerosis (MS). Advances in MRI techniques such as Double Inversion Recovery (DIR), Fluid Attenuated Inversion Recovery (FLAIR) and T2 Weighted Imaging (T2WI) sequences made it more sensitive to distinguish and investigate the lesion load on different anatomical regions of the brain .MRI is used as a strong tool to record the history of the disease and evaluate the response to treatment. Methodology: A total of 97 MS patients were included in our retrospective study, confirmed by neurologist. The patients were randomly selected from the major hospital in Saudi Arabia. All images were obtained using 3T Scanner (Siemens Skyra). The images from the DIR, FLAIR, and T2WI sequences were compared on axial planes with identical anatomic position and the number of lesions were assigned to their anatomical region. Statistical analysis was done using IBM SPSS statistics software version 25.0. To determine association and linear relationship, nonparametric method for comparison such as Friedman’s analysis of variance by rank and Wilcoxon-test and Spearman correlation were used Results: Majority of our patients suffered from the duration of the disease between 2 to 3 years (44.3%). The frequency analysis for types of the MS among patients represented that the majority (n=87) of the patients were at Relapsing Remitting MS. Comparing the lesion load measurement at various brain anatomical regions showed a significant difference among those three methods (P<0.05). The highest number of lesions in all anatomical regions belonged to DIR with a mean number (M=37.67) which was significantly higher than other sequences followed by FLAIR (M=29.57) which was significantly higher than T2WI (M=27.47). DIR was highly sensitive in detection of intracortical lesions (M=2.35) with a better delineation between grey matter/white matter margins in different anatomical areas. The highest contrast ratio in all anatomical regions belonged to DIR which was significantly higher than other sequences followed by T2WI which was significantly higher than FLAIR, except for Lesion/CSF which FLAIR showed the highest ratio. The correlation between the number of lesions and EDSS in DIR in infratentorial region (r= 0.584, p<0.001) was strong, positive and significant and the highest sensitivity of the DIR sequence (92.9% at the cut-off points of "4.5") with an accuracy of 0.883 (p<0.001) and specificity of 73.5% was observed in infratentorial region. Conclusion: DIR is a valuable MRI sequence for better delineation, greater contrast measurements and the increasing total number of MS lesions in MRI, compared with FLAIR and T2WI and DIR revealed more intracortical lesions as well, therefore, in MS patients it is recommended to add DIR sequence in daily routine imaging sequences.